2022
DOI: 10.1002/eat.23769
|View full text |Cite
|
Sign up to set email alerts
|

Identifying eating disorders in adolescents and adults with overweight or obesity: A systematic review of screening questionnaires

Abstract: Objective: This review aimed to examine the validity of self-report screening questionnaires for identifying eating disorder (ED) risk in adults and adolescents with overweight/obesity. Method: Five databases were searched from inception to September 2020 for studies assessing validation of self-report ED screening questionnaires against diagnostic interviews in adolescents and adults with overweight/obesity. The review was registered with PROSPERO (https://www.crd.york.ac.uk/PROSPERO/display_record. php?Recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 87 publications
(349 reference statements)
0
17
0
Order By: Relevance
“…Current assessment of risk for atypical anorexia nervosa and bulimia nervosa in individuals with overweight and obesity may be limited as assessment tools designed to detect restrictive eating disorders have been developed in lower weight populations and may not have adequate sensitivity when used for individuals with overweight or obesity 78 . Additionally, there is a lack of guidance for clinicians as to how best to assess and monitor eating disorder risk in people with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current assessment of risk for atypical anorexia nervosa and bulimia nervosa in individuals with overweight and obesity may be limited as assessment tools designed to detect restrictive eating disorders have been developed in lower weight populations and may not have adequate sensitivity when used for individuals with overweight or obesity 78 . Additionally, there is a lack of guidance for clinicians as to how best to assess and monitor eating disorder risk in people with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, case reports in adolescents have shown that recognition and diagnosis of atypical anorexia nervosa can be delayed during weight loss attempts as complications may occur at a higher body weight 77. Future trials of behavioral weight management should monitor for the emergence or disordered eating behaviors across the full spectrum of eating disorders.Current assessment of risk for atypical anorexia nervosa and bulimia nervosa in individuals with overweight and obesity may be limited as assessment tools designed to detect restrictive eating disorders have been developed in lower weight populations and may not have adequate sensitivity when used for individuals with overweight or obesity 78. Additionally, there is a lack of guidance for clinicians as to how best to assess and monitor eating disorder risk in people with overweight and obesity.…”
mentioning
confidence: 99%
“…The EDE was originally published more than three decades ago, and remains among the most widely used interviews for assessing ED symptoms, particularly in ED-focused research. 218 , 219 Core benefits of using the EDE interview among adolescents include: the ability to clarify complex concepts with interviewees who may find certain abstract concepts difficult to comprehend; potentially improving recall via careful orientation to the timeframe captured by the interview; ability to mitigate inattentive or impulsive responding; accounting for external factors that could impact responding (eg, family and cultural context, parent/guardian-influenced food/eating rules); and improved diagnostic accuracy over self-report questionnaires. However, as with any semi-structured interview-based assessment, the EDE requires more extensive training and is associated with greater burden given the time necessary to complete the interview.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of literature to guide the assessment of and change in eating disorder risk in individuals with overweight or obesity. Few studies have validated self-report eating disorder questionnaires against a structured clinical interview in people with overweight or obesity (38). Thus, it is challenging to identify normative data in this population to ascertain appropriate cut-points indicating someone may be at risk of, or may meet diagnostic criteria for an eating disorder.…”
Section: Defining Change In Eating Disorder Risk [H3]mentioning
confidence: 99%